Team leadership across contexts: a qualitative study - Graça, A. (2015)
Purpose – The purpose of this paper is to compare leadership functions from different team contexts considering context characteristics that contribute to team effectiveness. Design/methodology/approach – A qualitative study was conducted. Seven leaders of multidisciplinary child protection teams (MDTs) and nine managers of an information technology (IT) company took part in semi-structured interviews. The data were analyzed using content analysis with ATLAS.ti. Findings – Results showed that the two types of teams used different performance criteria, with teams from non-profit contexts lacking defined performance criteria. The results also showed that transition leadership functions are more frequently mentioned by IT than by MDT leaders. Moreover, interpersonal leadership functions emerged as independent functions that may occur in both the transition and action phases. Research limitations/implications – Context is paramount for performance criteria definition and for the relevance of certain team leadership functions over others. It also presents some suggestions for improvement to the model of Morgeson et al. (2010a). Practical implications – The results support the idea that there are differences in the leadership functions that are most valued by leaders, depending on the specific team’s context. Results also showed that some non-profit and less task-structured teams lack the specific performance criteria that could help them make more successful interventions. Originality/value – This paper reviews context literature, it shows that the emphasis on team leadership functions can vary across contexts and to the knowledge it is the first that compares the model of Morgeson et al. (2010a) in different contexts.